Adapting decarbonylation chemistry for the development of prodrugs capable of in vivo delivery of carbon monoxide utilizing sweeteners as carrier molecules. Issue 31 (16th July 2021) - De La Cruz, Ladie Kimberly; Yang, Xiaoxiao; Menshikh, Anna; Brewer, Maya; Lu, Wen; Wang, Minjia; Wang, Siming; Ji, Xingyue; Cachuela, Alyssa; Yang, Haichun; Gallo, David; Tan, Chalet; et al.
Abstract : 1, 2-Dicarbonyl compounds with FDA-approved sweeteners as leaving groups deliver CO for protection against acute kidney injury in mice. Abstract : Carbon monoxide as an endogenous signaling molecule exhibits pharmacological efficacy in various animal models of organ injury. To address the difficulty in using CO gas as a therapeutic agent for widespread applications, we are interested in developing CO prodrugs through bioreversible caging of CO in an organic compound. Specifically, we have explored the decarboxylation–decarbonylation chemistry of 1, 2-dicarbonyl compounds. Examination and optimization of factors favorable for maximal CO release under physiological conditions led to organic CO prodrugs using non-calorific sweeteners as leaving groups attached to the 1, 2-dicarbonyl core. Attaching a leaving group with appropriate properties promotes the desired hydrolysis–decarboxylation–decarbonylation sequence of reactions that leads to CO generation. One such CO prodrug was selected to recapitulate the anti-inflammatory effects of CO against LPS-induced TNF-α production in cell culture studies. Oral administration in mice elevated COHb levels to the safe and efficacious levels established in various preclinical and clinical studies. Furthermore, its pharmacological efficacy was demonstrated in mouse models of acute kidney injury. These studies demonstrate the potential of these prodrugs with benign carriers as orally active CO-based therapeutics. This represents the very first example of orally active organic CO prodrugs with a benign carrier that is an FDA-approved sweetener with demonstrated safety profiles in vivo .